Effect of Slag Gypsum Binder as a Substitute to Cement on the Stability of Backfill Mining - Xiaobing, Yang; Zepeng, Yan; Weiguang, Li; Leiming, Wang; Shenghua, Yin (Frontiers in Materials, 2022)
To effectively apply slag-gypsum binder (SGB) to most modern mines. An experimental study is conducted to investigate the feasibility and reliability of slag-gypsum binder (SGB) to replace cement in the mine backfill to effectively apply SGB in modern mines. The optimum parameters of aggregate and SGB fineness were investigated on laboratory basis and the effect of concentration on the workability was analysed. Also, industrial tests were carried out to study the cementitious properties of SGB and compared to cement. Finally, the hydration properties of SGB were analyzed using XRD and SEM. The results indicated that the main hydration products of SGB are C-S-H gel and ettringite, while Ca(OH)2 is consumed during the hydration process. And the structure formed in the later stage of SGB is more compact. SGB is beneficial to the strength of the waste rock mixture. The sample prepared with the waste rock-rod milling sand-river sand mixture has a maximum strength of 7.54 MPa at 28 d. Reducing fineness is beneficial to form early strength. However, a specific surface area exceeding 510 m2/kg will harm the later strength. Surface area is less (400 m2/kg) , the sample strength decreases when the dosage increase. Comparing the workability of SGB slurry and cement slurry, it is found that there is no essential difference between them under different mass concentration conditions. SGB slurry shows better fluidity and stability at a mass concentration of 80% to 82%. Industrial backfill experiments show the 3 d, 7 d, and 28 d strengths of SGB samples under 80% mass concentration conditions are 0.91 times, 1.43 times, and 1.2 times the cement samples. Therefore, using SGB instead of cement to backfill has a good application prospect.